Kinematic Outcome Measures using Target-Reaching Arm Movement in Stroke - Qianqian Yang; Yuan Yang; Jie Luo; Le Li; Tiebin Yan; Rong Song (Annals of Biomedical Engineering, 2017)

The oxidative DNA damage response: A review of research undertaken with Tsinghua and Xiangya students at the University of Pittsburgh - Arthur S. Levine; Luxi Sun; Rong Tan; Ying Gao; Lu Yang; Hao Chen; Yaqun Teng; Li Lan (Science China Life Sciences, 2017)

Erratum to: Activation of the ventral tegmental area increased wakefulness in mice - Huan-Xin Sun; Dian-Ru Wang; Chen-Bo Ye; Zhen-Zhen Hu; Chen-Yao Wang; Zhi-Li Huang; Su-Rong Yang (Sleep and Biological Rhythms, 2017)

Expression of HopAI interferes with MAP kinase signalling in Magnaporthe oryzae - Xue Zhang; Wende Liu; Yang Li; Guotian Li; Jin‐Rong Xu (Environmental Microbiology, 2017)
Summary The Pmk1 and Mps1 MAP kinases are essential for appressorium formation and plant infection in Magnaporthe oryzae . However, their exact roles during invasive growth are not clear because pmk1 and mps1 mutants are defective in penetration. To further characterize their functions after penetration, in this study we expressed the Pseudomonas syringae effector HopAI known to inactivate plant MAP kinases in M. oryzae . Constitutive expression of HopAI with the RP27 or TrpC promoter resulted in defects in hyphal growth, conidiation, appressorium penetration and pathogenicity, which is similar to the phenotype of the mps1 mutant. HopAI interacted strongly with Mps1 in vivo and expression of dominant active MKK2 partially suppressed the defects of P RP27 ‐HopAI transformants, which were significantly reduced in Mps1 phosphorylation. When the infection‐specific MIR1 ( Magnaporthe ‐infection‐related gene‐1) promoter was used to express HopAI, P MIR1 ‐HopAI transformants were defective in the spreading of invasive hyphae and elicited strong defense responses in penetrated plant cells. Expression of HopAI in Fusarium graminearum also mainly affected the activation of Mgv1, an Mps1 orthologue. Taken together, our results showed that Mps1 is the major intracellular target of HopAI when it is overexpressed, and MAP kinase signalling is important for cell‐to‐cell movement of invasive hyphae in M. oryzae .

Phenotypic Variation and Genetic Diversity in the Collections of Erianthus Arundinaceus (Retz.) Jesw. - Xi-Hui Liu; Huan-Zhong Song; Ge-Min Zhang; Wei-Xing Duan; Rong-Hua Zhang; Yang-Rui Li (Sugar Tech, 2017)

The levels of DNGR-1 and its ligand-bearing cells were altered after human and simian immunodeficiency virus infection - Wen-Rong Yao; Dong Li; Lei Yu; Feng-Jie Wang; Hui Xing; Gui-Bo Yang (Immunologic Research, 2017)

Response of performance and bacterial community to oligotrophic stress in biofilm systems for raw water pretreatment - Li-juan Feng; Rong Jia; Jing-ya Sun; Jing Wang; Zheng-hui Lv; Jun Mu; Guang-feng Yang (Biodegradation, 2017)

Temperature‐mediated local adaptation alters the symbiotic function in arbuscular mycorrhiza - Rong Yang; Xiaobu Cai; Xiaolin Li; Peter Christie; Junling Zhang; Jingping Gai (Environmental Microbiology, 2017)
Summary Variation in the symbiotic function of arbuscular mycorrhizal fungi (AM fungi) has been demonstrated among distinct biotic and abiotic interactions. However, there is little knowledge on how local temperature conditions influence the functional divergence of AM symbionts in alpine ecosystems. Here, we conduct a reciprocal inoculation experiment to explore the three‐way interactions among plants, AM fungal inoculum and temperature at sites of contrasting elevation. Evidence of local adaptation of plant growth was found only under low temperature conditions, with no consistent local versus foreign effect found in AM fungal performance. The origin of either the plant or the inoculum relative to the temperature was important in explaining symbiotic function. Specifically, when inoculum and temperature were sympatric but allopatric to the plant, poor adaptation by the plant to the novel environment was clearly found under both temperature conditions. Further analysis found that the symbiotic function was inversely related to fungal diversity under high temperature conditions. These results suggest that local adaptation represents a powerful factor in the establishment of novel combinations of plant, inoculum and temperature, and confirms the importance of taking into account both biotic and abiotic interactions in the prediction of the response of symbionts to global environmental change.

Copper-modified palygorskite is effective in preventing and treating diarrhea caused by Salmonella typhimurium - Da-wei Yao; Ze-zhong Yu; Na Li; Yu-nong Hou; Jia-rong Xu; De-ji Yang (Journal of Zhejiang University-SCIENCE B, 2017)

Activation of the ventral tegmental area increased wakefulness in mice - Huan-Xin Sun; Dian-Ru Wang; Chen-Bo Ye; Zhen-Zhen Hu; Chen-Yao Wang; Zhi-Li Huang; Su-Rong Yang (Sleep and Biological Rhythms, 2017)

MEF2D Mediates the Neuroprotective Effect of Methylene Blue Against Glutamate-Induced Oxidative Damage in HT22 Hippocampal Cells - Zi-wei Chen; Anmin Liu; Qingyu Liu; Jingkao Chen; Wen-ming Li; Xiao-juan Chao; Qian Yang; Pei-qing Liu; Zi-xu Mao; Rong-biao Pi (Molecular Neurobiology, 2017)

Transient Receptor Potential-canonical 1 is Essential for Environmental Enrichment-Induced Cognitive Enhancement and Neurogenesis - Lai-Ling Du; Lin Wang; Xi-Fei Yang; Ping Wang; Xiao-Hong Li; Da-Min Chai; Bing-Jin Liu; Yun Cao; Wei-Qi Xu; Rong Liu; Qing Tian; Jian-Zhi Wang; et al. (Molecular Neurobiology, 2017)

Pathophysiological Responses in Rat and Mouse Models of Radiation-Induced Brain Injury - Lianhong Yang; Jianhua Yang; Guoqian Li; Yi Li; Rong Wu; Jinping Cheng; Yamei Tang (Molecular Neurobiology, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Use of stable isotopes to understand food webs in Macao wetlands - Qian Chen; Yang Liu; Wei-Tim Ho; Shek Kiu Chan; Qiu-hua Li; Jian-Rong Huang (Wetlands Ecology and Management, 2017)

Performance improvement of raw water pretreatment process with pre-inoculation biofilm: feasibility and limiting factors - Guang-feng Yang; Li-juan Feng; Cai-rong Guo; Tian Xia; Xiang-yang Xu; Liang Zhu (Biodegradation, 2017)

Abnormal O-GlcNAcylation of Pax3 Occurring from Hyperglycemia-Induced Neural Tube Defects Is Ameliorated by Carnosine But Not Folic Acid in Chicken Embryos - Rui-Rong Tan; Yi-Fang Li; Shi-Jie Zhang; Wen-Shan Huang; Bun Tsoi; Dan Hu; Xin Wan; Xuesong Yang; Qi Wang; Hiroshi Kurihara; Rong-Rong He (Molecular Neurobiology, 2017)

Contamination, Fractionation and Biological Risk Related to Metals in Surface Sediments from the Largest Deep Freshwater Lake in China - Hua-Bing Li; Yang-Guang Gu; Rong Wang; Hui-Bin Lu (Archives of Environmental Contamination and Toxicology, 2017)